Growing Up in Scotland: Sweep 2 - Parenting Styles and Parental Support - Government, Scottish (Scottish Government, 2008)
Research findings (of four) accompanying the full research report on Sweep 2 findings of the Growing Up in Scotland study Year 2
Keywords: Demographic trends; Parents and parenting